2020
DOI: 10.1017/s0954102020000553
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Erebus volcano's thermal energy to power year-round monitoring

Abstract: Year-round monitoring of Erebus volcano (Ross Island) has proved challenging due to the difficulties of maintaining continuous power for scientific instruments, especially through the Antarctic winter. We sought a potential solution involving the harvesting of thermal energy dissipated close to the summit crater of the volcano in a zone of diffuse hot gas emissions. We designed, constructed and tested a power generator based on the Seebeck effect, converting thermal energy to electrical power, which could, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…A similar system, intended to power the year-round monitoring system of the Erebus volcano, Ross Island, was presented in the article [39]. The construction of the harvester was analogous to the one previously described; a thermoelectric transducer and heat exchangers with thermal conductors were used.…”
Section: Volcanic Energymentioning
confidence: 99%
“…A similar system, intended to power the year-round monitoring system of the Erebus volcano, Ross Island, was presented in the article [39]. The construction of the harvester was analogous to the one previously described; a thermoelectric transducer and heat exchangers with thermal conductors were used.…”
Section: Volcanic Energymentioning
confidence: 99%
“…The most complicated task is powering a remote instrument year-round because of many factors [5]: (i) solar radiation changes during the year from whole days of sun during the Antarctic summers to complete darkness during winters; (ii) strong winds, often unpredictable in duration and strength, which can cause severe issues when wind turbines are used as power sources; (iii) the cold temperatures, which decrease the capacity of most batteries. An interesting solution to maintain continuous power for scientific instruments was recently proposed by [7], who suggested to use the harvesting of thermal energy collected near the summit crater of the Erebus volcano.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, since a low power supply is required compact, autonomous and robustly, binary cycles are not a viable option. As an alternative, thermoelectric generators have been proposed in the literature [9,10] due to their robustness and durability even without maintenance, as demonstrated in spatial applications [11]. Catalan et al demonstrated their viability in reality, with a prototype that produced between 0.32 and 0.33 W in an 82 • C fumarole [12].…”
Section: Introductionmentioning
confidence: 99%